2020 International Conference on Artificial Intelligence and Data Analytics for Air Transportation (AIDA-At) 2020
DOI: 10.1109/aida-at48540.2020.9049181
|View full text |Cite
|
Sign up to set email alerts
|

A Map-Matching Algorithm for Ground Movement Trajectory Representation using A-SMGCS Data

Abstract: Increasing availability of air traffic data has opened new opportunities for better understanding of Air Traffic Management (ATM) system. At Airport-Air side, A-SMGCS (Advanced Surface Movement Guidance & Control System) data may provide useful insights to improve efficiency and safety of airport operations by understanding traffic patterns, taxiway usage, ground speed profiles and any anomaly behaviour. However, A-SMGCS data comes from the fusion of several sensors such as MLAT, ADS-B and SMR. This leads to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The position and velocity of the aircraft in intervals of roughly one second are available in cartesian coordinates and WGS-84 coordinates. To make this data suitable for analysis, all the aircraft trajectories are mapped onto a geometric network using the map-matching methodology proposed by Tran, Pham, and Alam (2020). Then, the avoided conflicts are detected and divided into a train and test set for machine learning.…”
Section: Methodsmentioning
confidence: 99%
“…The position and velocity of the aircraft in intervals of roughly one second are available in cartesian coordinates and WGS-84 coordinates. To make this data suitable for analysis, all the aircraft trajectories are mapped onto a geometric network using the map-matching methodology proposed by Tran, Pham, and Alam (2020). Then, the avoided conflicts are detected and divided into a train and test set for machine learning.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the first pre-processing step is to apply a map-matching algorithm to standardize the trajectory data and remove noise and outliers. The applied map-matching algorithm (adopted from author's previous work [47]) includes two steps -spatial matching and temporal map-matching. In spatial matching, the tracking positions of the aircraft are matched with the airport-airside network to obtain a taxi-route that is the graph representation of aircraft movement as a sequence of taxi segments.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…Each trajectory represents aircraft movements in spatial and temporal domains. It is, however, observed that the raw data contains a lot of noise (irregularity in positional coordinates over time) and missing information which is pre-processed, map matched and cleaned [7], [39], [40]. Post cleaning, 60% of the data remains which is used for simulation purposes (refer TABLE I).…”
Section: B Extracting Aircraft Taxi Routes Using A-smgcs Datamentioning
confidence: 99%
“…The airside network is represented by graph G(N, E) [39] where edges E represent taxiways (and runways) that are connected at nodes N . The graph G(N, E) in this study is constructed from public OpenStreeet map data [41] following the methodology outlined in [39], [40]. The resulting Changi Airport graph contains 518 nodes and 1686 edges (refer Fig.…”
Section: A Airside Networkmentioning
confidence: 99%